2021
DOI: 10.3389/fmed.2021.708453
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effects of Heme Oxygenase-1 in Kidney Disease

Abstract: Kidney disease is a general term for heterogeneous damage that affects the function and the structure of the kidneys. The rising incidence of kidney diseases represents a considerable burden on the healthcare system, so the development of new drugs and the identification of novel therapeutic targets are urgently needed. The pathophysiology of kidney diseases is complex and involves multiple processes, including inflammation, autophagy, cell-cycle progression, and oxidative stress. Heme oxygenase-1 (HO-1), an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 218 publications
(237 reference statements)
0
14
0
Order By: Relevance
“…HO-1 can be expressed in renal tubular epithelial cells and leukocytes in response to oxidative stress [ 17 ] and hemolysis [ 18 , 19 ]. Macrophages are the pre-dominantly HO-1 expressing cells [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…HO-1 can be expressed in renal tubular epithelial cells and leukocytes in response to oxidative stress [ 17 ] and hemolysis [ 18 , 19 ]. Macrophages are the pre-dominantly HO-1 expressing cells [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…HO-1 can be expressed in renal tubular epithelial cells and leukocytes in response to oxidative stress [ 17 ] and hemolysis [ 18 , 19 ]. Macrophages are the pre-dominantly HO-1 expressing cells [ 19 ]. HO-1 expression in the kidney was determined by immunofluorescence after moderate and severe renal IRI and different time-points after ECMO.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Free heme influences innate immune responses through the activation of Toll-like receptor 4 and ROS-dependent pathways, which in turn, through complex signaling pathways, promote the expression of proinflammatory cytokines. In addition, heme degradation byproducts (CO, biliverdin, bilirubin) and HO-1 constitute key molecules that upregulate the secretion of anti-inflammatory cytokines, such as IL-10 [ 13 ] ( Figure 2 ). On the other hand, many pro-inflammatory enzymes, such as cyclooxygenase-2 (COX-2) and inducible nitric oxide synthase (iNOS), are in fact hemoproteins whose functions may be impaired due to insufficient free heme once that heme has been catalyzed by HO-1 [ 14 ].…”
Section: Ho-1 and Iga Nephropathymentioning
confidence: 99%
“…Μonocytes from patients with SLE—independently of disease activity—displayed significantly reduced HO-1 levels compared to those of healthy controls, suggesting that this low HO-1 expression and action could contribute to altered monocyte function in SLE and lupus nephritis. [ 13 ]. Kishimoto et al have also demonstrated that glomerular M2-like macrophages from LN patients exhibit lower levels of HO-1 expression.…”
Section: Ho-1 and Lupus Nephritismentioning
confidence: 99%